Molecular Dynamics Simulations of the Cardiac Troponin Complex Performed with FRET Distances as Restraints - Jayasundar, Jayant James; Xing, Jun; Robinson, John M.; Cheung, Herbert C.; Dong, Wen-Ji (PLOS ONE, 2014)
Cardiac troponin (cTn) is the Ca2+-sensitive molecular switch that controls cardiac muscle activation and relaxation. However, the molecular detail of the switching mechanism and how the Ca2+ signal received at cardiac troponin C (cTnC) is communicated to cardiac troponin I (cTnI) are still elusive. To unravel the structural details of troponin switching, we performed ensemble Förster resonance energy transfer (FRET) measurements and molecular dynamic (MD) simulations of the cardiac troponin core domain complex. The distance distributions of forty five inter-residue pairs were obtained under Ca2+-free and saturating Ca2+ conditions from time-resolved FRET measurements. These distances were incorporated as restraints during the MD simulations of the cardiac troponin core domain. Compared to the Ca2+-saturated structure, the absence of regulatory Ca2+ perturbed the cTnC N-domain hydrophobic pocket which assumed a closed conformation. This event partially unfolded the cTnI regulatory region/switch. The absence of Ca2+, induced flexibility to the D/E linker and the cTnI inhibitory region, and rotated the cTnC N-domain with respect to rest of the troponin core domain. In the presence of saturating Ca2+ the above said phenomenon were absent. We postulate that the secondary structure perturbations experienced by the cTnI regulatory region held within the cTnC N-domain hydrophobic pocket, coupled with the rotation of the cTnC N-domain would control the cTnI mobile domain interaction with actin. Concomitantly the rotation of the cTnC N-domain and perturbation of the D/E linker rigidity would control the cTnI inhibitory region interaction with actin to effect muscle relaxation.